Limits on Patient Responsibility - M. . Kelley (Бюллетень сибирской медицины)
As we debate the nature and extent of patient responsibility it is important to keep in mind the reasons for giving a relatively minimal role to patient responsibility in medical ethics. It is argued that the medical profession ought to be characterized by two moral asymmetries: even if some degree of responsible behavior from patients is called for, placing the dominant emphasis on pro- fessional responsibility over patient responsibility is largely correct; insofar as we do want to encourage an increase in patient re- sponsibility, we have good reasons to emphasize prospective rather than retrospective notions of responsibility in clinical practice. Concerns about patient vulnerability along with the determined factors in disease leave little room for blame at the bedside. These two asymmetries generate normative limits on any positive account of patient responsibility.